Implementasi Database Terdistribusi Pada Sistem Penggajian CV. Rejeki Jaya Makmur Abadi dengan Metode Replikasi Multimaster Dan Fragmentasi Horizontal - Lamidja, Richeldo M. Pitna; Wismarini, Th Dwiati (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Information systems and computerized technology are currently developing very rapidly so that this gives an idea of agencies being able to adapt according to the times, one of which is CV Rejeki Jaya Makmur Abadi with various kinds of innovations that are starting to be implemented. Aiming to produce applications that can run on various platforms, sometimes ignoring the value of the information that will be presented. Without realizing it, damage to the data presented can actually result in huge losses. Replication is the process of copying and maintaining database objects, such as tables, in many databases that form a distributed database system. Changes made to one location are recorded and stored locally before being forwarded and applied to every other location. In this article, we will discuss the implementation of database replication in the CV payroll system. eternal prosperous fortune using multimaster replication and horizontal fragmentation methods.